Superflux of an organic adlayer towards its local reactive immobilization - Salamon, David; Bukvišová, Kristýna; Jan, Vít; Potoček, Michal; Čechal, Jan (NATURE PORTFOLIO, 2023)
On-surface mass transport is the key process determining the kinetics and dynamics of on-surface reactions, including the formation of nanostructures, catalysis, or surface cleaning. Volatile organic compounds (VOC) localized on a majority of surfaces dramatically change their properties and act as reactants in many surface reactions. However, the fundamental question "How far and how fast can the molecules travel on the surface to react?" remains open. Here we show that isoprene, the natural VOC, can travel similar to 1 mu m s(-1), i.e., centimeters per day, quickly filling low-concentration areas if they become locally depleted. We show that VOC have high surface adhesion on ceramic surfaces and simultaneously high mobility providing a steady flow of resource material for focused electron beam synthesis, which is applicable also on rough or porous surfaces. Our work established the mass transport of reactants on solid surfaces and explored a route for nanofabrication using the natural VOC layer.
Keywords: BEAM-INDUCED DEPOSITION; FOCUSED ELECTRON-BEAM; SURFACE-DIFFUSION; CARBON CONTAMINATION; MOLECULES; SPECTROSCOPY; LITHOGRAPHY; FABRICATION; MICROSCOPY; SPILLOVER